Bentuk Origami Modular pada Struktur Lipat - S., Beta Suryokusumo; Putranto, Ary Deddy; Wibisana, Iwan (RUAS, 2013)
Long-span architecture can be a consideration when we need a large interior and long span architecture. Thorugh the inspiration of nature and hand working, it can be one way to create folding construction. One of the reconzed hand arts is origami. Origami which deliberated to modular origami can be identified by design, firmness, and function. The result are developeing folded plate combine by modular origami techniques as a modelling and digital result. through origami, the finding result is origami provide a data base as design criterias and three model of basic folded plateKeywords: the art of origami, modular shape, folded strucure